Clinical Impact of Minimal Micropapillary Pattern in Invasive Lung Adenocarcinoma. (May 2015) - Lee, Geewon; Lee, Ho Yun; Jeong, Ji Yun; Han, Joungho; Cha, Min Jae; Lee, Kyung Soo; Kim, Jhingook; Shim, Young Mog
<x xml:space="preserve">Abstract</x> Micropapillary subtype has recently been established to be a distinct marker for poor prognosis in lung adenocarcinomas. According to the current classification of lung adenocarcinomas, all subtypes are listed semiquantitatively in 5% increments. In other words, a minimal amount of the micropapillary pattern, precisely <5% of the entire tumor is disregarded. Therefore, we sought to assess the prognostic significance and survival outcomes in patients with a micropapillary pattern proportion of <5% of the entire tumor. A total of 525 patients with lung adenocarcinoma were classified into 3 subgroups according to the presence and proportion of micropapillary subtype: (1) ≥5% of the micropapillary pattern (n=114); (2) <5% of the micropapillary pattern (n=115); and (3) absence (<1%) of the micropapillary pattern (n=296). Sex, TNM stage, lymph node status (N status), tumor size, and predominant subtype demonstrated a significant difference among the 3 subgroups. Overall survival (OS) and disease-free survival (DFS) were significantly different among the 3 subgroups (P=0.009 and 0.001 for OS and DFS, respectively). Furthermore, OS was significantly better in patients without the micropapillary pattern (<1%) than in those with <5% (P=0.034). At multivariate analyses, age (P=0.005) and N status (P=0.005) were independent prognostic factors influencing OS. In conclusion, our results demonstrated that even a small proportion of the micropapillary pattern, specifically <5% of the entire tumor has a significant prognostic impact on OS. N status remained an independent prognostic factor that negatively influenced OS.